2011
DOI: 10.5625/lar.2011.27.2.147
|View full text |Cite
|
Sign up to set email alerts
|

OCT4 Expression Enhances Features of Cancer Stem Cells in a Mouse Model of Breast Cancer

Abstract: The cancer stem cell (CSC) hypothesis proposes that CSCs are responsible for metastasis and disease recurrence. Therefore, targeting CSCs has the potential to significantly improve outcomes for cancer patients. The OCT4 transcription factor gene is a master gene that plays a key role in the self-renewal and pluripotency of stem cells. In this study, we introduced an OCT4 reporting vector into 4T1 mouse breast cancer cells and sorted OCT4 high and OCT4 low cell populations. We then determined whether OCT4 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 25 publications
6
99
0
Order By: Relevance
“…In addition, Oct4 has been implicated in various human cancers and was reported to be associated with tumor progression or bad prognosis (12)(13)(14)(15)(16)(17). The present study demonstrated that the mRNA and protein expression of Oct4 was higher in human lung cancer tissues than that in adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Oct4 has been implicated in various human cancers and was reported to be associated with tumor progression or bad prognosis (12)(13)(14)(15)(16)(17). The present study demonstrated that the mRNA and protein expression of Oct4 was higher in human lung cancer tissues than that in adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 52%
“…108 Indeed, Oct4 is expressed in a subpopulation of breast and ovarian cancer cells that possess self-renewal ability, 109,110 and Oct4 overexpression is sufficient to enhance tumor-propagating cells in a mouse model of breast carcinoma. 111 Beltran et al recently confirmed that the sole transduction of Oct4 in primary human mammary epithelial breast cell preparations from reduction mammoplasty donors was sufficient to generate cell lines possessing tumor-initiating and colonization capacities. Moreover, the Oct4-transduced breast cells displayed a gene signature compatible with that of claudin-low breast carcinomas, which is a molecular subtype of breast cancer that is highly enriched in cancer stem cell-like features.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have shown that Oct-4 activates transcription via the octamer motif of an AGTCAAAT consensus sequence, and affects mammalian development by regulating the pluripotent potential of stem cells (3)(4)(5)(6)(7). Subsequent studies have demonstrated that Oct-4 is also expressed in a number of types of tumor cells, and that it has potential as a biomarker for the diagnosis and prognosis of malignant tumors (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Further studies have indicated that Oct-4 may be important in cancer cell survival, and that it exerts multiple functions in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Oct-4 functions as a master switch during differentiation, by regulating the pluripotent potential of stem cells, and that it is important during mammalian development. Other studies have demonstrated that Oct-4 is expressed in various types of human tumor, including gastric cancer (8,9), breast cancer (10), non-small cell lung carcinoma (11), glioma (12)(13)(14), esophageal squamous cell carcinoma (15) and certain types of testicular germ cell tumors (16,17). Furthermore, aberrant expression of Oct-4 has been shown to be involved in maintaining self-renewal, and the cancer stem cell-like, and chemoradioresistant properties of lung cancer (18).…”
Section: Introductionmentioning
confidence: 99%